Reklamasi Iman dalam Puasa Ramadhan - Robingun Suyud El Syam; Salis Irvan Fuadi (LP3M KH Yazid Karimullah Institute, 2023)
Ramadan fasting creates lifestyle changes for those who live it, the physical benefits have been produced by many researchers. Interesting how Ramadan fasting changes the dimension of faith, so this study aims to explore Ramadan fasting as a reclamation of faith. This article is the result of findings from a qualitative type of literature research, taking the theory of reclamation in relation to faith, then analyzing it inductively to produce conclusions. The results of the study show: Ramadan fasting is a reclamation of faith where the order is intended for believers to become pious individuals both in the individual and social dimensions, manifesting in changes and increasing faith towards a better and more meaningful direction in their lives. The implications of research on the importance of faith are manifested in real behavior in the reality of life, more detailed indicators of increasing faith in Ramadan fasting are needed for further research. The research is expected to contribute to the development of Islamic education in the study of the dimensions of faith through Ramadan fasting